Creative edutainment learning application for elementary students using exploratory approach - Ng, Wei Li (2022)
Last decade, the advancement of technologies has a rapid growth in the world. The integration of technologies and education brings the advantages to the education sector. One of the examples is the interactive multimedia application. Interactive multimedia provides an interesting environment for learners to learn. The concept of 'learning while playing', also called as edutainment, able to help the learners to learn faster and enhance their memories. Instead of learning the textual lesson in classroom, learners able to learn in an enjoyable environment by interacting with the colourful graphics and animations. Besides, the interactive learning application applied with technologies able to stimulate the students' thinking and imagination. By learning with the applications, students also manage to explore more creativity idea that able to apply in their daily life. This project is aimed to develop an edutainment learning application for elementary students who aged from eight to nine years old. This application This application does not limit the gender of the students as both female and male students can be using it. The topic of the proposed application is to let the students learning the plants and insects in a creative way rather than learning it from a textbook. Various multimedia elements such as animation, graphics and audio will be included in this application in order to make the learning environment interesting and attractive. Besides, there will be an augmented reality (AR) view for the each plant and insect. This feature helps to improve the cognitive skill of learners by assimilating the objects into the real environment. In order to develop this proposed application, the methodology used is ADDIE model which consists of five phases. The phases are analysis, design, development, implementation and evaluation.